2009
DOI: 10.1063/1.3204453
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and temperature dependence of photoluminescence of m-plane GaN grown on γ-LiAlO2 (100) substrate

Abstract: We investigated the polarization and temperature dependence of photoluminescence ͑PL͒ of m-plane GaN grown on ␥-LiAlO 2 ͑100͒ substrate. The calculated electronic band structure with k • p Hamiltonian points out the energy splitting as well as polarization selection originate from the m-plane GaN epilayer under anisotropic strain. The polarization-angle dependence PL spectra are found to be selected from in-plane x-and z-polarized emission, corresponding to T 1 and T 2 transition. And the intensity distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Among them, the polarized light emission has attracted interest due to its various applications such as back light unit for liquid crystal display, high‐contrast imaging, and improving the performance of laser diodes . It has been theoretically or experimentally reported that GaN semiconductor under anisotropic in‐plane strain exhibited modified valence band structures and resultant polarized optical properties . Through the subsequent efforts of previous researchers, the linearly polarized light emissions have been achieved from non‐/semi‐polar InGaN/GaN multiple quantum wells (MQWs) grown on non‐/semi‐polar bulk GaN or foreign substrates .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the polarized light emission has attracted interest due to its various applications such as back light unit for liquid crystal display, high‐contrast imaging, and improving the performance of laser diodes . It has been theoretically or experimentally reported that GaN semiconductor under anisotropic in‐plane strain exhibited modified valence band structures and resultant polarized optical properties . Through the subsequent efforts of previous researchers, the linearly polarized light emissions have been achieved from non‐/semi‐polar InGaN/GaN multiple quantum wells (MQWs) grown on non‐/semi‐polar bulk GaN or foreign substrates .…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been previously proposed to achieve polarized light emission from III-nitride LEDs. For example, it has been widely reported that a high degree of intrinsic linearly polarized light emission can be obtained from LED structures grown on nonpolar/semipolar substrates. , However, it suffers from the high cost of nonpolar/semipolar substrates, as well as the high density of basal stacking faults and threading dislocations in the material . Other reports have demonstrated that highly polarized luminescence can be obtained through the integration of nanostructures, such as metal gratings, combined dielectric/metal structures, and photonic crystals .…”
mentioning
confidence: 99%